Effect of new direct-acting antiviral drugs on insulin resistance and glycemic control after treatment of chronic hepatitis C virus infection in type 2 diabetic patients - Alaa E.M Hashim; Hanaa T Kandeel; Olfat M Hendy; Khaled El-Mola; Fathyia M El-Raey; Mohamed S.M Attia (Al-Azhar Assiut Medical Journal, 2017)
Background Hepatitis C virus (HCV) infection is associated with diabetes and may worsen glycemic control in patients with diabetes. The benefits of eradicating HCV infection with direct-acting antiviral (DAAs) may go well beyond avoiding the damage caused by chronic liver inflammation, to include declines in glycated hemoglobin percent and other metabolic parameters. The present study was designed to evaluate the effect of new DAAs drugs, used for treatment of HCV, on insulin resistance and glycemic control at the end of treatment and 3 months after end of treatment of HCV infection in patient with type 2 diabetic mellitus (T2DM) in Damietta Governorate. Patients and methods This study included 75 T2DM patients with chronic HCV infection. Patients were divided according to level of glycosylated hemoglobin percent into three groups. All patients received DAAs and were monitored by A1C%, homeostasis model assessment-insulin resistance, and fasting blood sugar before, at the end of treatment, and 12 week after the end of treatment. Patients were allocated into two groups: the first group included 57 (76%) patients with improved glycemic control (IGC) and the second group included 18 (24%) patients with nonimproved glycemic control (NIGC). Results In IGC group, 45 (78.9%) patients needed to decrease the dose of antidiabetic treatment. There were no significant differences between IGC and NIGC groups regarding sex and liver condition. The percentage of patients with old age, those with positive family history of T2DM, and those with long duration of T2DM were significantly higher in NIGC group compared with IGC. Conclusion Diabetic patients receiving DAAs should be closely monitored during reduction of antidiabetic drugs, especially regarding insulin and sulfonylurea, to avoid hypoglycemic events. Improvement of glycemic control with DAAs is seen more in younger patients without family history of T2DM and short duration of diabetes mellitus.